2008
DOI: 10.1387/ijdb.072396ls
|View full text |Cite
|
Sign up to set email alerts
|

Sex-determining mechanisms in insects

Abstract: Sex determination refers to the developmental programme that commits the embryo to either the male or the female pathway. The animal kingdom possesses a wealth of mechanisms via which gender is decided, all of which are represented among the insects. This manuscript focuses on a number of insects for which genetic and molecular data regarding sex determination mechanisms are available. The sex determination genetic cascade of Drosophila melanogaster is first discussed, followed by an analysis of the sex determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
214
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(220 citation statements)
references
References 137 publications
4
214
0
2
Order By: Relevance
“…some Lepidoptera [46 ]) and paternal X chromosome inactivation (e.g. coccids (Homoptera) and Sciarid flies [1 ]). Whether and how tra regulation occurs in these groups remains an interesting unanswered question.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…some Lepidoptera [46 ]) and paternal X chromosome inactivation (e.g. coccids (Homoptera) and Sciarid flies [1 ]). Whether and how tra regulation occurs in these groups remains an interesting unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“…Green boxes indicate species from which only dsx has been reported but presence of tra has been inferred from sequence data. Blue box indicates species in which a feminizing gene has been found but no dsx or tra yet (modified after [1 ]). …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Second, previous studies have shown that dsx has a highly conserved function as the terminal gene in the sex determination pathway that regulates the sex-limited expression of downstream genes, leading to sexually dimorphic development and behavior across diverse insects (7)(8)(9). The structure and function of dsx are best understood from studies in Drosophila.…”
mentioning
confidence: 99%